A sensitive fluorescent assay based on gold-nanoclusters coated on molecularly imprinted covalent organic frameworks and its application in malachite green detection. (1st June 2023) - Zhao, Lehan; Lin, Xianfeng; Duan, Nuo; Mahmood Khan, Imran; Wang, Zhouping; Wu, Shijia
Highlights: Fluorescent assay based on AuNCs coated on molecularly imprinted COFs was developed. COFs, served as skeletons, provided stable and multiple binding sites for MIPs. A satisfactory detection limit of 2.78 nmol/L for MG was achieved by this assay. It can be successfully applied to the MG analysis in water and fish samples. Fluorescence resonance energy transfer (FRET) occurred between AuNCs and MG. Abstract: Malachite green (MG), as a parasiticide, is widely used in aquaculture to increase the production of the fishery industry. It poses a great danger to both the food system and the human body. In this study, a one-pot reverse microemulsion polymerization was employed to combine the gold nanoclusters (AuNCs) with molecularly imprinted polymers (MIPs) and covalent organic frameworks (COFs) to synthesize an efficient fluorescent hybrid probe (AuNCs@COFs@MIPs) for selective detection of MG. The specific recognition of AuNCs@COFs@MIPs towards MG triggers the fluorescence quenching of AuNCs. The fluorescent response was linearly related to the concentration over the range of 10–150 nmol/L with a limit of detection of 2.78 nmol/L. In addition, the proposed probe was further applied to fish and water samples. A favorable recovery ranged from 97.34 to 101.51 % toward trace amounts of MG indicating its promising application for detecting residue of veterinary drugs.